The Influence of Environmental, Social, and Governance (ESG) Disclosure on Financial Performance - Nyoman Cantika DEWI; Ida Ayu SURASMI; Komang Adi Kurniawan SAPUTRA (PT Keberlanjutan Strategis Indonesia, 2025)
The banking sector plays an instrumental role in maintaining the stability of the financial system through its crucial intermediary function between corporate entities and borrowers. Consequently, companies that actively engage in ESG disclosure tend to exhibit superior financial performance due to their ability to mitigate risks, enhance operational efficiency, and bolster their reputation. This study empirically examines the effect of environmental, social, and governance (ESG) disclosure on the financial performance of banking companies listed on the IDX for 2020–2023. Using purposive sampling, 96 companies were selected. Multiple linear regression analysis was applied. The results indicate that Environmental Disclosure has a positive and significant effect on Financial Performance, with a significance value of 0.000 < 0.05 and a positive regression coefficient of 4.134. Similarly, Social Disclosure positively and significantly affects Financial Performance, with a significant value of 0.0008 < 0.05 and a positive regression coefficient of 4.233. Governance Disclosure also has a positive and significant impact on Financial Performance, with a significance value of 0.0001 < 0.05 and a positive regression coefficient of 4.021. The Adjusted R² value of 0.568 indicates that 56.8% of financial performance is influenced by Environmental, Social, and Governance Disclosure, the remaining 43.2% is explained by external factors outside of this research.